2019
DOI: 10.1101/777169
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fingerprints of cancer by persistent homology

Abstract: We have carried out a topological data analysis of gene expressions for different databases based on the Fermat distance between the z scores of different tissue samples. There is a critical value of the filtration parameter at which all clusters collapse in a single one. This critical value for healthy samples is gapless and smaller than that for cancerous ones. After collapse in a single cluster, topological holes persist for larger filtration parameter values in cancerous samples. Barcodes, persistence diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In physics, topological voids (đť“— 2 structures) were found in the study of the baryon acoustic oscillation related to the galaxy distribution ( Kono, Takeuchi, Cooray, Nishizawa, & Murakami, 2020 ). Finally, in medicine, Carpio, Bonilla, Mathews, and Tannenbaum (2019) use the topological descriptors for the two first dimensions, that is, đť“— 0 and đť“— 1 . They found that different cancer cells have distinct topological values at these dimensions, indicating the descriptors’ usefulness as biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In physics, topological voids (đť“— 2 structures) were found in the study of the baryon acoustic oscillation related to the galaxy distribution ( Kono, Takeuchi, Cooray, Nishizawa, & Murakami, 2020 ). Finally, in medicine, Carpio, Bonilla, Mathews, and Tannenbaum (2019) use the topological descriptors for the two first dimensions, that is, đť“— 0 and đť“— 1 . They found that different cancer cells have distinct topological values at these dimensions, indicating the descriptors’ usefulness as biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 5 shows the existence of an interesting number of features that are not spurious. Therefore, extending the analysis of loops to a percentage of the most persistent could provide a new perspective for the analysis, because with more cycles, it is possible to (a) enrich the R-fMRI topological description of each subject, which can be used in other developments like classification ( Bhaskar et al, 2021 ; Carpio et al, 2019 ), and (b) identify the nodes that are involved in more than one persistent loop because they could be relevant in the study of brain high-order processes. Another concern is the use of the proposed approach for comparison between population and/or specific brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the increasing availability of medical data related to all sorts of illnesses is fostering the development of machine learning techniques [2] for medical diagnosis and treatment. While neural networks are often used for image based diagnosis [25,16], supervised and unsupervised clustering techniques [22] are now widely employed to investigate the role of genes in sickness [17,24,4,20] and to study the response to therapies [15,6], as well as for assisted clinical diagnosis using information from digital devices [18,21]. Developing tools to assess the reliability of such automatic procedures and to choose the best method for different situations and clinical environments has become essential [18].…”
Section: Introductionmentioning
confidence: 99%
“…Topological Data Analysis (TDA) arises naturally in several fields like surface reconstruction [23], quasi periodicity classification in video data and other time series [53,54,58], protein formation [31,60], identification of tumors [8], detection of stock market crashes [33], algebraic computational geometry [18], and many others. Understanding topological features from data is also crucial in the experimental study of chaotic dynamical systems since the main strategy to validate or reject a physical model in the presence of chaotic behavior is to determine if the data and the model itself share the same topology [5,32,47,48,50].…”
mentioning
confidence: 99%